SPECT/CT imaging of hNIS-expression after intravenous delivery of an oncolytic adenovirus and 131I. - Maria Rajecki (Public Library of Science (PLoS), 2012)
Oncolytic adenoviruses can be engineered for better tumor selectivity, gene delivery and be armed for imaging and concentrating radionuclides into tumors for synergistic oncolysis. We constructed Ad5/3-hTERT-hNIS where replication is controlled by hTERT-promoter. Ad5/3-hTERT-hNIS expresses hNIS for imaging of transgene expression and for treatment of infected tumors by radioiodine. Ad5/3-hTERT-hNIS efficiently killed prostate cancer cells and induced iodine uptake in vitro and in vivo after intratumoral virus administration. Survival of mice treated with intravenous Ad5/3-hTERT-hNIS significantly prolonged survival over mock or radioiodine only but the combination of virus with radioiodine was not more effective than virus alone. Temporal and spatial changes in hNIS-expression during therapy were detected with SPECT, demonstrating feasibility of evaluation of the combination therapy with hNIS-expressing adenoviruses and radioiodide.